Damage threshold determination and non-destructive identification of possible failure sites in PIN limiter - Tan, Cher Ming (2014)
In this work, we employ a circuit simulation tool to investigate the signature of the change in S-parameters curves with the degradation of PIN limiter circuit parameters. Unique correlations can be established for all the circuit parameters, and this provides a good way to identify possible failure sites before destructive physical analysis of the degraded limiters.